Mapping the Behavior Patterns of Public Space Users on the Alley: (Case: Kampung Heritage Kayutangan, Malang) - Savitri, Diana; Nugroho, Agung Murti; Titisari, Ema Yunita; Omar, Shida Irwana (RUAS, 2025)
Urban public spaces are essential for meeting the community's needs for comfort and social interaction. Urban density contributes to the lack of public space, so the remaining public space must be used optimally. In Kayutangan Heritage, Malang, Indonesia, public spaces are used for domestic activities with private characteristics and for tourist activities with public characteristics. Optimizing the use of public space, especially the alley in the Kampung Heritage Kayutangan alley, requires planning and control to prevent conflicts and ensure available spaces support both functions in a balanced manner. This study identifies the behavior patterns of public space users in Kampung Kayutangan using behavior mapping. Through direct observation, the researcher collected data on the use of alleys as public spaces, including activity types, gathering points, territories, and timing. The data is compiled in a place-centered mapping format. The results of the study show the spots in public space that are the centers of activity, the variety of activities, their intensity, and the territories they occupy. The results of this study contribute to the optimal and context-based planning and development of public spaces in tourism kampung (based on community needs), especially in Kayutangan Heritage Kampung.